Unani medicine in the making: practices and representations in 21st-century India - Schmidt Stiedenroth, Kira (Amsterdam University Press, 2020)
Cover -- Table of Contents -- Acknowledgements -- Introduction -- Multiplicity, Practice Ontology, and Looping Effects -- Unani and Traditional Medicine in South Asia -- The Biomedicalization of Traditional Medicines -- Theory vs. Practice? -- From the Topic to Fieldwork -- Conducting Fieldwork -- Sources and Methods -- 1. A System of Medicine? -- Official Representations of Unani Medicine -- Government Institutions and Official Publications -- The Prescription of Drugs -- The National Formulary of Unani Medicine and the Unani Pharmacopoeia of India -- Unani Practitioners -- Doctors or Hakims? -- The Old Ḵẖandānī Hakim as Embodiment of Unani Knowledge -- The Cult of Eminent Hakims -- The Unani Fraternity -- Textual Sources of Authority -- Systematization and Looping Effects -- The Systematization of (Unani) Medicine: Historical Overview -- Enactments and Loopings -- 2. Authority, Originality, and the Limits of Standardization -- Creation and Transmission of Medical Knowledge -- Becoming a Hakim -- Institutionalized Training and its Shortcomings -- Family Lineages and Secret Knowledge -- Degrees and (Un-)Official Practice -- The Regulation of Practice -- Qualified and Registered Practitioners -- BUMS as Second Choice -- Practicing 'Allopathy' with a Unani Degree -- Defying Standards -- Individualized Treatments and Clinical Falsification -- Pulse Diagnosis and the Limits of Standardization -- Exclusive Knowledge and the Pursuit of Originality -- Standardized Drugs -- Variations of Medicine and Multiplicity -- 3. Beyond Humouralism -- Fundamental Principles of Unani Medicine -- The Concept of Medicine and the Principles of Human Physiology -- 'What is First' -- Diseases -- Treatments and Prevention -- Finding the Root Cause of Disease -- Observation and Questioning -- Pulse Examination.
Description based on publisher supplied metadata and other sources
Keywords: Yunani; Indien; Medizin; Islam